ANTI-TUMOR EFFECTS OF EPHEDRINE AND ANISODAMINE ON SKBR3 HUMAN BREAST CANCER CELL LINE - Chen, Dan; Ma, Feng; Liu, Xiao-hui; Cao, Rui; Wu, Xiong-Zhi (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: To investigate the effects of ephedrine and anisodamine on the proliferation of human breast cancer. Materials and Methods: SKBR3 cell was treated with or without ephedrine and / or anisodamine, respectively. The trypan blue exclusion assay was used to determine cell numbers. Flow cytometry was used to assess cell cycle distribution and apoptosis. The concentration of cAMP and cyclin D1 was analyzed by enzyme-linked immunosorbent assay. Western blot was used to measure PKA. Results: Ephedrine and anisodamine inhibited cell proliferation and arrested SKBR3 cells at G0/G1 phases. Ephedrine and anisodamine increased the level of CD1 in SKBR3 cells. Furthermore, significant change in intracellular cAMP concentration was found in SKBR3 cells treated with ephedrine and anisodamine. The phosphorylation of PKA substrate was not activated after 48 hours of treatment with ephedrine and anisodamine. Conclusion: Ephedrine and anisodamine inhibit the proliferation of SKBR3 cells via a significantly change of intracellular cAMP concentration.